Contener el espacio: Densificar + Conectar + Contener (2020)
Contener el espacio Contain the space, is an urban renewal project that seeks to revitalize the south western sector of the Military School in the locality of Barrios Unidos. The project arises as part of the extension of Carrera 58 proposed in the master plan of the section, that intends to break the physical and social limits that currently exist between the different neighborhoods and populations of the sector (Entre Ríos, Los Andes, Rionegro), by connecting Calle 80 with Calle 100. Today, the southern side of the road presents great challenges as it is home to several large-scale endowment facilities (Military School, Buen Pastor Prison, Episcopal Conference). Facilities that have large green spaces but are completely isolated from the rest of the city by multiple kilometers of walls and bars. These physical conditions generate little activity and social interaction in the street in addition to a strong sense of hostility and insecurity. Due to these reasons, the project seeks to open these green spaces to the rest of the city by proposing an architecture that encourages social interaction and encourages activity in the street based on 3 fundamental strategies: Densify, Connect and Contain. The result are 3 residential blocks, with a great variety of complementary uses, which aim to respond adequately to the different scales, populations, and uses of the sector through an architecture with different heights and typologies that offers an excellent experience and quality of life for all residents and visitors of the sector.